The Network Concept of Creativity and Deep Thinking: Applications to Social Opinion Formation and Talent Support. (July 2017) - Csermely, Peter
Our century has unprecedented new challenges, which need creative solutions and deep thinking. Contemplative, deep thinking became an "endangered species" in our rushing world of Tweets, elevator pitches, and fast decisions. Here, we describe how important aspects of both creativity and deep thinking can be understood as network phenomena of conceptual and social networks. "Creative nodes" occupy highly dynamic, boundary spanning positions in social networks. Creative thinking requires alternating plasticity-dominated and rigidity-dominated mind-sets, which can be helped by dynamically changing social network structures. In the closing section, we present three case studies which demonstrate the applications of the concept in the Hungarian research student movement, the Hungarian Templeton Program, and the Youth Platform of the European Talent Support Network. These examples show how talent support programs can mobilize the power of social networks to enhance creative, deliberative, deep thinking of talented young minds, influencing social opinion, leading to community action, and developing charismatic leadership skills.